Toxicity of amphetamine-type drugs in rat cardiomyocyte cells involves oxidative stress and the formation of acidic vesicular organelles - Valente, M. J.; Araújo, A. M.; Carvalho, F.; Carvalho, M. (Scientific Letters, 2023)
Background: Synthetic cathinones (SCs) are recreational psychoactive substances with pharmacological properties resembling those of classical amphetamines, such as 3,4-methylenedioxymethamphetamine (MDMA; ecstasy) [1]. Although the use of SCs has been linked to adverse health outcomes, including myocardial infarction and sudden cardiac deaths [2], the underlying cardiotoxic mechanisms are still unknown. Objective: This study evaluates the potential in vitro cardiotoxicity mechanisms of two commonly abused SCs, 3,4-methylenedioxypyrovalerone (MDPV) and 3,4-methylenedioxymethcathinone (methylone), and compares them with those obtained for MDMA. Methods: The H9c2 cell line was exposed for 24 hours to a wide range of concentrations (0.01-15 mM for MDPV; 0.01-20 mM for MDMA and methylone). The cytotoxic response was measured through the MTT assay and the role of oxidative stress was evaluated through the production of reactive oxygen and nitrogen species (ROS/RNS). The formation of acidic vesicular organelles (AVOs) was also evaluated by fluorescence microscopy in cells exposed to EC30 or EC60 of each drug. Results: All compounds decreased cell viability in a concentration-dependent manner. MDPV and MDMA were the most toxic drugs (EC50 1.76, 1.86 mM, respectively), while methylone was the least cardiotoxic derivative (EC50 3.30 mM; p<0.0001 vs. EC50 MDMA; p<0.0001 vs. overall fit MDMA). MDMA triggered ROS/RNS production only at 0.8 mM (p<0.0001 vs. control) and MDPV only at 1.6 and 3 mM (p<0.01 vs. control). In contrast, methylone demonstrated a significant increase for all concentrations between 0.05 mM (p<0.0001 vs. control) and 12 mM (p<0.05 vs. control). All drugs prompted the formation of AVOs in a concentration-dependent manner. Conclusions: Our findings are the first to show that SCs cause in vitro cardiotoxicity, and that oxidative stress and autophagy may play a role in these events. Further research is needed to explore the underlying molecular mechanisms.